Black Beauty - Sewell, Anna (Lahore : Maqbool books, 2020)
Black Beauty by Anna Sewell is the autobiographical story of a horse named Black Beauty, told from his perspective. The novel follows Black Beauty$1 (Bs life journey, from his carefree days as a colt on an English estate, to his later experiences as a working horse in various settings. Through his encounters with different owners and his observations of other horses, Black Beauty learns about kindness, cruelty, and the varying treatment of horses in society. The novel highlights the importance of humane treatment and compassion toward animals, particularly horses. It portrays the harsh realities of the mistreatment of animals in the 19th century, as well as the positive impact of kindness and respect. Black Beauty aims to raise awareness about animal welfare and promote empathy and responsible stewardship toward animals.s
Keywords: English : Novel